2016
DOI: 10.1002/glia.22989
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 43 in astrocytes contributes to motor neuron toxicity in amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by progressive loss of motor neurons in the CNS. Astrocytes play a critical role in disease progression of ALS. Astrocytes are interconnected through a family of gap junction proteins known as connexins (Cx). Cx43 is a major astrocyte connexin conducting crucial homeostatic functions in the CNS. Under pathological conditions, connexin expression and functions are altered. Here we report that an abnormal increase in Cx43 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
127
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(145 citation statements)
references
References 62 publications
17
127
1
Order By: Relevance
“…Activated HCs have been involved in the release of gliotransmitters such as ATP and glutamate as well as chemokines that have deleterious consequences on neurons as reported in murine models of AD [18][19][20], experimental allergic encephalomyelitis [21], amyotrophic lateral sclerosis [20,22] and neuropathic pain [23,24]. In our study, it has also been demonstrated that activated HCs can allow Ca 2+ influx, contributing to a maintenance of high [Ca 2+ ]i.…”
Section: Commentarysupporting
confidence: 73%
“…Activated HCs have been involved in the release of gliotransmitters such as ATP and glutamate as well as chemokines that have deleterious consequences on neurons as reported in murine models of AD [18][19][20], experimental allergic encephalomyelitis [21], amyotrophic lateral sclerosis [20,22] and neuropathic pain [23,24]. In our study, it has also been demonstrated that activated HCs can allow Ca 2+ influx, contributing to a maintenance of high [Ca 2+ ]i.…”
Section: Commentarysupporting
confidence: 73%
“…Similarly to astrocytes (15,19,(32)(33)(34), however, we report that oligodendrocytes affect MNs through two distinct mechanisms of action: soluble factors and cell-to-cell contact, with the latter being more aggressive. Addition of lactate to the cocultures, in fact, does not rescue MNs.…”
Section: Discussionmentioning
confidence: 70%
“…In mutant SOD1 animals, astrocyte Cx43 is significantly upregulated with disease progression, whereas oligodendrocyte Cx32 and Cx47 are downregulated (110,111). These changes in glial network activity through connexin hemichannels could contribute to the failure of remyelination and eventual demise of motor neurons.…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E Nmentioning
confidence: 99%